2018
DOI: 10.3390/catal8020083
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of Benzyl Alcohol on a Strontium-Based Gold Material: Remarkable Intrinsic Basicity and Reusable Catalyst

Abstract: The development of stable and active gold catalysts has arisen as a significant strategy for oxidation of alcohols. Nano-size PVA-stabilized gold nanoparticles immobilized on Sr(OH) 2 by colloidal deposition presented high catalytic activity for benzyl alcohol oxidation. In 2.5 h, 2 bar of O 2 and without extra-base addition, the calcined support reached 54.6% (100 • C) and 67.4% (140 • C) of conversion, presenting the remarkable and unexplored intrinsic basicity that strontium-based materials retain. With sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
3
0
4
Order By: Relevance
“…Because of the manageable numbers, scholarships were handled mainly by a deliberative council that would analyse candidates in the face of the available funding. According to Darcy Closs, CAPES' executive director from 1974 to 1979, this process was particularly challenging, as many national figures would pressure the council to award grants to proteges (Castro;Soares, 1983;Córdova, 2001;Moreira, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the manageable numbers, scholarships were handled mainly by a deliberative council that would analyse candidates in the face of the available funding. According to Darcy Closs, CAPES' executive director from 1974 to 1979, this process was particularly challenging, as many national figures would pressure the council to award grants to proteges (Castro;Soares, 1983;Córdova, 2001;Moreira, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, the single committee would not be able to keep up with the number of scholarships granted every year, which grew more than 400% in less than a decade (Castro;Soares, 1983). Therefore, two significant changes were implemented:…”
Section: Introductionmentioning
confidence: 99%
“…The drawback related to the use Au catalyst is the need to operate under alkaline conditions, which facilitate the first step of the oxidative dehydrogenation (H abstraction), however making purification a challenge and limiting the industrial application [18,19]. Recent studies have shown that the support can play a key role in enhancing the activity and the selectivity of the gold catalyzed reactions, even in absence of a base [20,21,22,23,24]. Indeed, the support surface properties can tune the interaction with the metallic particles, modifying both the catalysts electronic and structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, outros desafios como a corrosão severa levam ao incremento dos custos de produção e manutenção [24]. Deste modo, o desenvolvimento de novos catalisadores heterogêneos é uma melhor proposta para a melhoria dos processos catalíticos que envolvem oxidação de álcoois [25]- [28].…”
Section: Catálise Heterogêneaunclassified
“…Por outro lado, a utilização de um meio fortemente alcalino, pode ser considerado uma restrição ao uso de catalisadores de Au, uma vez que podem ocorrer reações colaterais como equilíbrio ceto-enol, reação de Cannizaro, descarbonilação oxidativa, as quais diminuem a seletividade do catalisador, ou ainda promover danos no catalisador [46]. Para evitar tais inconvenientes tem-se promovido a combinação das nanopartículas de Au com um segundo metal como por exemplo Pd ou Pt, o que evita a necessidade de utilizar uma base [25].…”
Section: Uso Do Ouro Na Catálise Heterogêneaunclassified